2015
DOI: 10.5582/irdr.2015.01035
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex cytokine analysis of Werner syndrome

Abstract: We reported a minor inflammation-driven ageing (inflammageing) assessed by highly sensitive CRP (hsCRP) in normal individuals and patients with Werner syndrome (WS), followed by an ageing associated Th2-biased cytokine change in normal ageing in the previous papers. To further study the association of hsCRP and 26 cytokines/chemokines in 35 WS patients, a multiple cytokine array system was used in the same serum samples as were examined for hsCRP. The serum levels of Th2 cytokines (IL-4, IL-6, IL-10, and GM-CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The body initiates the immune response by secreting proinflammatory cytokines such as IL‐2, IL‐6, and IL‐8. As an innovative cytokine detection technique, the Luminex bead array system allows us to quantitatively detect multiple cytokines in a single test using a minimal level of samples . In the present study, cytokine responses to HTNV infection were monitored and the patient cytokine profiles were used to access the outcome of HFRS treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The body initiates the immune response by secreting proinflammatory cytokines such as IL‐2, IL‐6, and IL‐8. As an innovative cytokine detection technique, the Luminex bead array system allows us to quantitatively detect multiple cytokines in a single test using a minimal level of samples . In the present study, cytokine responses to HTNV infection were monitored and the patient cytokine profiles were used to access the outcome of HFRS treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As the recent WS gene (WRN) knock-out mice study suggested an induction of immune dysfunction followed by chronic inflammation (30), we would like to speculate that the loss-of-function mutation of WRN may lead to some immune dysfunction leading to more susceptibility to CMV infection in WS than normal aging populations. Because natural killer cell function declined significantly in WS and WS patients produced more auto-antibodies compared with the normal aging population as we already reported (4,5,8,9,(31)(32)(33)(34)(35). Obviously, this is a highly speculative idea and further study may be needed to clarify the pathogenesis of mild inflammation: inflammageing in healthy aging and also in WS.…”
Section: Discussionmentioning
confidence: 73%
“…Chronic elevation of hsCRP in the normal elderly population may probably be associated with agingrelated pathological conditions including diabetes mellitus (DM), sarcopenia, osteoporosis, cancer, atherosclerosis, cognitive decline and finally death (6,7). Aging-related persistent, systemic, minimal and asymptomatic inflammation, termed 'inflammageing', is tightly associated with an imbalance between an increase in pro-and a decrease in anti-inflammatory substances including cytokines/chemokines (8)(9)(10)(11). Inflammation is widely recognized as a pathophysiologically fundamental metabolism to generate energy with thermogenesis, leading to wound healing and tissue destruction during healthy development and aging (6,12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation alters intercellular communication owing to the accumulation of cytokines increasing with aging. Patients with WS have elevated cytokine levels of interleukin-2 (IL-2), IL-4, IL-6, tumor necrosis factor alpha (TNF-α), interferon gamma (IFNγ), and monocyte chemoattractant protein-1 (MCP-1) 18 .…”
Section: Introductionmentioning
confidence: 99%